Secular Civic or Individual Achievement? Reconsidering Educational Value Orientations in Indonesia - Ramdani Putri Setyaningrum (Perkumpulan Alumni dan Santri Mahyajatul Qurro’, 2026)
This study examines what Indonesian adults believe education should cultivate in children and identifies the social and demographic factors that shape these beliefs. Using data from the Indonesian component of the World Values Survey Wave 7 conducted in 2018, this paper employs Principal Component Analysis (PCA) to construct two latent dimensions of educational value orientation and Ordinary Least Squares (OLS) regression to estimate their determinants among 3,200 respondents. Contrary to Inglehart and Welzel’s emancipative values theory, the PCA reveals two dimensions that do not conform to the predicted conformist-emancipatory dichotomy: a Secular Civic Orientation (SCO), capturing preferences for responsibility and diligence dissociated from religious faith, and an Individual Achievement Orientation (IAO), capturing preferences for imagination and tolerance dissociated from altruism. Education consistently increases SCO and decreases IAO, inverting the theoretical prediction. Female respondents score significantly higher on SCO, while older respondents score lower, suggesting a generational shift toward secular civic values. Interaction analyses confirm that these effects are uniform across urban-rural contexts, gender, and generational cohorts. Critically, the 2018 data provide an irreplaceable pre-reform baseline, positioning this study as the empirical starting point for evaluating the impact of the Merdeka Belajar curriculum reform and the COVID-19 pandemic on Indonesian educational values.